CFD-Based Thermal Performance of a Metal Casting Furnace for Vocational Education Laboratories - Rochmad Novian Inderanata; Fajar Dwi Yudanto; Arif Bintoro Johan; Setuju; Ibnu Saputro (Program Studi Pendidikan Teknik Mesin Fakultas Keguruan dan Ilmu Pendidikan Universitas Sriwiajaya, 2026)
This study aims to: (1) design and analyze the thermal performance of a charcoal-fueled crucible melting furnace as a teaching aid for vocational high schools (SMK); (2) evaluate combustion dynamics, temperature distribution, and the effect of mass flow rate variations on thermal efficiency using CFD simulation; and (3) describe the educational potential of the furnace as a practical platform for introducing heat transfer, fluid mechanics, and sustainable energy systems. This was a research and development (R & D) study. The furnace geometry was modeled using Autodesk Inventor Professional 2022, and its thermal performance was simulated using ANSYS Fluent 2021 R2. The model reliability was ensured through mesh-independence testing and finite element validation, followed by experimental validation to assess agreement with numerical results. The results show that the optimal combustion condition occurred at a mass flow rate of 0.001 kg/s, producing a peak temperature exceeding 1600°C, indicating suitability for non-ferrous metal melting. Experimental measurements confirmed strong alignment with the simulation outputs, with deviations remaining within acceptable tolerance limits, supporting the reliability of the proposed design and numerical approach for vocational learning applications.